Extrapulmonary Latent Tuberculosis Reactivation After Negative Screening Tests in a Liver Transplant Recipient. Issue 3 (May 2018) - Gonzales Zamora, Jose Armando; Patil, Sanjeev; Murali, Arvind R.; Hoehnen, Sarah
Abstract : Background: Posttransplant tuberculosis (TB) is an uncommon complication following liver transplantation (LT). Given its high mortality, it is advocated to screen for latent TB with tuberculin skin test (TST), interferon γ release assay and/or chest radiography before LT. Case Report: A 52-year-old Filipino gentleman was admitted with an 8-week history of abdominal pain, hematochezia, and weight loss. His pre-LT screening for latent TB with TST and chest radiography was negative. Colonoscopy revealed an ulcerated polypoid lesion in the terminal ileum. The cause of ulceration was histologically indeterminate. Because a lymphoproliferative disorder was suspected, a right hemicolectomy was done during which hard white studding was noted in the distal small bowel. Induration and a mass formation in the terminal ileum and the cecum were also seen. Histopathology showed necrotizing granulomas. Stain for acid–fast bacilli was negative. The strong suspicion for TB prompted us to obtain a chest computed tomography scan, which showed calcified perivascular and left hilar lymph nodes reflecting prior granulomatous disease. QuantiFERON-TB Gold In-Tube Test was positive. Treatment with standard anti-TB regimen was initiated. Two weeks later, cultures from intestinal tissue grew Mycobacterium tuberculosis . The patient reported a complete resolution of his symptoms at 3-month follow-up. Conclusions: Chest computed tomography scan and interferon γ release assays in conjunction with TST and chest radiograph may improve the detection of latent TB in transplant candidates. Combining these tests to diagnose latent TB is a strategy that needs to be evaluated in future studies. Abstract : Post-transplant tuberculosis is an uncommon complication following liver transplantation (LT). Given its high mortality, it is recommended to screen for latent tuberculosis before LT. This case presents a 52-year-old man with a negative screening for latent TB by chest x-ray and tuberculin skin test who developed intestinal tuberculosis 2 years after transplant. This case reflects the poor sensitivity of regular screening methods and suggests that computed tomography scan and interferon gold gamma release assay may improve the yield of latent TB detection.